The Living-Body: Center of Orientation Self-World-Other - Maria Aparecida Viggiani Bicudo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
The central question of this paper is: "How and why is the living body assumed as the guiding center of the I-world-other in in Husserl's phenomenology?" The carried out study to pursue the direction indicated by that question was based on chapters three and four of Ideas Pertaining to a Pure Phenomenology and to a Phenomenological Philosophy, volume II (Husserl, 2002, 2005), paragraphs 35 to 47. The study of that text enables the presentation of Husserl’s ideas regarding the living-body, that address issues concerning the physicality of the body, its psychophysical dimensions, the constitution of values, and intersubjectivity.